The Analisis Kesesuaian dan Daya Dukung Ekosistem Terumbu Karang untuk Mendukung Pengelolaan Perikanan dan Ekowisata Bahari Berkelanjutan di Perairan Wambitema, Teluk Tanah Merah, Kabupaten Jayapura - Lolita Tuhumena; Khristhoper A. A. Manalu; Yan Maruanaya (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
The coral reef ecosystem in Wambitema Waters, Tanah Merah Bay, Jayapura Regency, plays an important role in supporting reef fisheries resources and marine ecotourism activities. Sustainable management of coral reef ecosystems is required to maintain ecological balance while supporting fisheries and tourism utilization. This study aimed to analyze the suitability and carrying capacity of coral reef ecosystem areas to support sustainable fisheries management and marine ecotourism in Wambitema Waters. The study was conducted using coral reef fish observations through underwater visual census (UVC), assessment of marine tourism suitability using the Tourism Suitability Index (TSI), and environmental carrying capacity analysis. The parameters measured included coral cover, reef fish abundance, life form diversity, water clarity, depth, and current velocity. The results identified 415 species of coral reef fish belonging to 36 families, indicating high biodiversity and relatively healthy coral reef ecosystem conditions. The suitability analysis showed that the study area was categorized as highly suitable (S1) for diving activities with an IKW value of 2.63, and suitable to highly suitable for snorkeling activities with an IKW value of 2.42. The environmental carrying capacity value was estimated at 809 visitors/day, while the effective utilization carrying capacity recommended for sustainable management was 81 visitors/day for each activity. These findings indicate that Wambitema Waters have strong potential for integrated management of fisheries resources and marine ecotourism based on conservation principles, environmental carrying capacity, and sustainable utilization of coral reef ecosystems.